The Effect of Employee Character and Job Satisfaction on Performance with Discipline As an Intervening Variable on SPBUu Employees in Dompu Regency - Lukman, Lukman; Hermanto, Hermanto; Sultan, Zulkifli (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2025)
The purpose of this study is to analyze and describe the Influence of Employee Character and Job Satisfaction on Employee Performance with Discipline as an Intervening Variable at Gas Stations in Dompu Regency. This study is classified as quantitative research with research respondents being gas station employees in Dompu Regency totaling 55 people. The research instruments are documentation and questionnaires developed from each theory underlying the research variables. The data collection procedure was carried out directly to the research respondents who were given a maximum of 2 hours to fill out the instrument. Structural Equation Modeling analysis with Partial Least Square (PLS). Research results Employee character has a significant effect on employee performance. Employee character does not have a significant effect on employee discipline. Job satisfaction has a significant effect on employee performance. Job satisfaction has a significant effect on employee work discipline. Work discipline does not have a significant effect on employee performance. Employee character has a significant effect on performance through employee discipline. Job satisfaction has a significant effect on performance through employee discipline at SPBU in Dompu Regency.